SPECIES COMPOSITION AND DISTRIBUTION OF ACROPORA CORALS IN NHA TRANG BAY AND ADJACENT WATERS - Tran, Duc Dien; Samoilov , K.Yu.; Dang, Do Hung Viet; Nguyen, Trinh Duc Hieu; Hoang, Thi Ngoc Anh; Nguyen, Phuong Lien; Vu, Viet Dung; Vo, Thi Ha; Tran, Van Bang (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Nha Trang Bay (Khanh Hoa, Vietnam) is widely recognized for its rich and diverse coral reef ecosystems, where Acropora corals play a foundational role in reef construction and ecological function. Nevertheless, these ecosystems are increasingly threatened by the combined effects of climate change and human-induced disturbances. This study shows the species composition and distribution of the coral genus Acropora in Nha Trang Bay and adjacent waters. A total of 10 sites were surveyed using SCUBA-based Reef Check methodology, focusing on coral identification through morphological and skeletal characteristics. The 29 species of Acropora recorded with significant species richness found at Hon Bac Island, Hon Chong–Dang Tat, and Dam Bay sites. However, degradation of the coral reef is also recorded at multiple sites, with Acropora species experiencing dramatic declines due to the global coral bleaching event of 2024. Despite these pressures, some areas like Dam Bay show potential for coral restoration. Among the surveyed sites, Hon Bac Island and the nearshore waters north of Hon Chong stand out as ecologically valuable areas due to their exceptional live coral cover and biodiversity. In particular, Dam Bay, a designated coral gene pool preservation site - plays a vital role in ongoing conservation efforts. In addition to providing baseline ecological data, the study offers key recommendations for conserving and restoring Acropora reefs in Nha Trang Bay, including the establishment of marine protected zones in biodiversity hotspots, implementation of targeted coral restoration programs, enhancement of long-term monitoring and early-warning systems, and promotion of science-based, community-supported conservation strategies in areas showing signs of natural recovery. The findings provide crucial baseline data for conservation planning, restoration strategies, and genetic resource preservation of Acropora in Southern Vietnam.